P3.256 Transmitted Resistance Among Individuals Recently Diagnosed with HIV/AIDS in the Metropolitan Region of Recife, Northeast of Brazil. (13th July 2013) - Cavalcanti, A Salustiano; Brito, A; Salustiano, D M; Lima, K O; Silva, S P; Diaz, R S; Lacerda, H R
Abstract : Background: The highly active anti-retroviral therapy (HAART) has increased survival of patients with HIV/AIDS. However, some individuals may present therapeutic failure due to a variety of factors, including transmitted antiretroviral resistance. Thus, the objective of the study was investigate frequency of primary resistance and recent infection among HIV-1 seropositive individuals at five Voluntary Counseling and Testing Centers (VCT) at Metropolitan Region of Recife in Northeast of Brazil. Methods: For RNA transcription to cDNA and PCR amplification with genetic sequencing of the product was carried out using the TRUGENE ® HIV-1 Genotyping Assay. The sequences were analysed using the software OpenGene ® DNA Sequencing System and ARV resistance mutations and subtypes were submitted to the Stanford HIV Drug Resistance Database and further confirmed by SIMPLOT v.2. The BED Calypte ® assay was carried out for detection of recent HIV infection. Results: A total of 130 samples were analysed. Most participants were males (56%) and aged 31–50 years. Median T CD4+ lymphocyte was 408 cells/mm 3 and viral load was 3, 683 copies/ml. Primary resistance rate was 4.6%. Recent infection rate was 23%. Mutations associated with resistance to NNRTI, NRTI and PIs occurred in 3.84%, 1.53% and 0.77%, respectively. Conclusions: The present study showed that 4.6% of the strains had transmitted antiretroviral resistance mutations, which coincides with the low resistance rates that have been found in Brazil. Despite a high prevalence of recent infection, there were no significant differences in the prevalence of mutations between the recent and chronic infection groups (p = 0.327).